How children's worship changed the church: ritualism, liturgy and children in the late nineteenth century Church of England - Haynes, Catherine M. (Routledge new critical thinking in religion, theology and biblical studies, 2026)
"This book charts nineteenth-century ceremonial and liturgical change through ritualists' involvement of children in Church of England services. It draws on previously unresearched records of how children participated in services and considers the way in which their influence as adults subsequently shaped Anglican liturgy, theology and ecclesiology. Children were famously 'seen and not heard' and, as such, are often found below the radar of studies of Victorian Anglicanism. This volume sheds valuable light on the role that child choristers and ritualist children's hymnody played in the rapid growth of choral music in parish churches, as well as providing evidence of children's influence on the early origins of the Parish Communion Movement. The book also examines the role which children's guilds and catechism services played in nineteenth-century Church of England mission, and briefly reviews the legacy of ritualists' sacramental mission found in current eucharistic mission services in the Church in Wales. It will be of particular interest to scholars of church history, liturgy, ecclesiology, theology and childhood"-- Provided by publisher